Orderly and Effective Insolvency Procedures. (International Monetary Fund, 1999)
Written by IMF's Legal Department, this book outlines the key issues involved in designing and implementing orderly and effective insolvency procedures, which play a critical role in fostering growth and competitiveness and may also assist in the prevention and resolution of financial crises. The book draws on lessons learned from firsthand experience by some of the IMF's 182 member countries. It includes an analysis of the major policy choices that countries need to address when designing an insolvency system, a discussion of the advantages and disadvantages of these choices, and a number of specific recommendations.